The effects of an increase in the retirement age on health care costs: evidence from administrative data - Johannes Geyer; Mara Barschkett; Peter Haan; Anna Hammerschmid (The European Journal of Health Economics, 2022)
In this paper, we use unique health record data that cover outpatient care and the associated costs to quantify the health care costs of a sizable increase in the retirement age in Germany. For the identification, we exploit a sizable cohort-specific pension reform which abolished an early retirement program for all women born after 1951. Our results show that health care costs significantly increase by about 2.9% in the age group directly affected by the increase in the retirement age (women aged 60–62). We further show that the cost increase is mainly driven by the following specialist groups: Ophthalmologists, general practitioners (GPs), neurology, orthopedics, and radiology. While the effects are significant and meaningful on the individual level, we show that the increase in health care costs is modest relative to the positive fiscal effects of the pension reform. Specifically, we estimate an aggregate increase in the health costs of about 7.7 million euro for women born in 1952 aged 60–62 which amounts to less than 2% of the overall positive fiscal effects of the pension reform.
Keywords: I10; I12; I18; J14; J18; J26; 610; Pension reform; Health care costs; Difference-in-differences